A Review of Avner Greif's Institutions and the Path to the Modern Economy: Lessons from Medieval Trade - Clark, Gregory (Journal of Economic Literature, 2007)
Avner Greif's Institutions and the Path to the Modern Economy: Lessons from Medieval Trade (Cambridge University Press, 2006) is a major work in the ongoing project of many economists and economic historians to show that institutions are the fundamental driver of all economic history and of all contemporary differences in economic performance. This review outlines the contribution of this book to the project and the general status of this long standing ambition.